Sistematización del diseño de un manual de funciones para la implementación de un proceso de selección de personal basado en competencias en La Empresa Grupo Mancheno Cia. Ltda. : en el periodo septiembre 2016 - agosto 2017 - Falconí Mantilla, Efrén Enrique (2018)
This project was conducted at Grupo Mancheno Cia. Ltda, a bussines that revolves around the production and commercialization of insurance packages. It has 10 years working in the field and currently employs 55 collaborators nationwide. Within its organizational structure, its Human Talent Management Departmnt was lacking proper processes and tools and was conducting its activities empirically and inefficiently; this in turn constantly endangered the company´s development and genereted dangerous sources of psychosocial unrest that effected the mental health of its collaborators. This systematization describes the results obtained by designingand implementing a functions manual and selection process based on competences. Then, through the analysis of the different methodological tools that were used in the project´s permanent and continuous management stages, we were able to verify if said tools manage to present options that generate growth and influence the business organization of Grupo Mancheno Cia. Ltda. The proposed methodology is mixed, since it uses both quantitative techniques and procedures. As a result, we notice a positive change reflected in the satisfaction of collaborators and management, thus showing that the project managed to achieve its objective and positively contribute to the psychosocial well-being of the company´collaborators while at the same time promoting their mental well- being.